The Effectiveness of Islamic-Based Rational Emotive Behavior Therapy Group Counseling to Improve Discipline and Reduce Student’s Procrastination - Chairunnisya, Chairunnisya; Sugiyo, Sugiyo; Sutoyo, Anwar (Jurnal Bimbingan Konseling, 2022)
Students’ tendency to violate discipline affects teaching and learning at school, such as procrastination of task completion or called as academic procrastination. This study aimed to examine the effectiveness of Islamic-based Rational Emotive Behavior Therapy (REBT) group counseling to improve discipline and reduce students’ procrastination. It used pretest-posttest control group design and involved 20 subjects from SMP Al-Musyaffa Kendal. Based on the results of Wilcoxon and Man-Whitney analyses, the Islamic-based Rational Emotive Behavior Therapy (REBT) group counseling could improve discipline and reduce procrastination. It infers that the Islamic-based Rational Emotive Behavior Therapy (REBT) group counseling implemented through the reinforcement of morals, praying, and fasting is effective in increasing discipline and reducing procrastination.